Embracing Representation: Integrating Canoeing and Female Swimming Adapted Sports in a Digital Game Platform - Silva, Daniel Espindola da; Brandão, André Luiz; Vittori, Karla (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na Educação, 2023)
The representation of individuals from diverse backgrounds in the media is a topic extensively discussed in literature, posing itself as a challenging area for investigation. Such representation can significantly influence whether a person chooses to engage with a particular application or not. Digital games serve as a crucial medium that offers opportunities to both learn various content and bring visibility to individuals from diverse profiles. However, the literature reveals a scarcity of digital games featuring characters with disabilities or special needs as protagonists. Therefore, this article presents a game that not only builds upon the existing modalities explored in previous studies but also introduces two additional modalities of adapted sports: canoeing and female swimming. The aim is to broaden the game’s scope, allowing it to reach an audience that has yet to be targeted, while simultaneously contributing to the discourse on representation in digital media. The game can be used to stard discussions about gender stereotypes, disabilities, representation and diversity in line with the the Brazilian “National Common Core Curriculum” (Base Nacional Comum Curricular - BNCC).